2017
DOI: 10.1136/bmjopen-2016-014240
|View full text |Cite
|
Sign up to set email alerts
|

Link between healthy lifestyle and psychological well-being in Lithuanian adults aged 45–72: a cross-sectional study

Abstract: ObjectiveThis study uses a cross-sectional study design to analyse the connection between psychological well-being (PWB) and components of a healthy lifestyle in the Lithuanian population aged 45–72. The purpose of our study is to establish the links between PWB and lifestyle factors such as physical activity, smoking, alcohol consumption and dietary patterns in people above the age of 44.ParticipantsA stratified sample of 10 940 urban citizens aged 45–72 years were randomly selected from the National Populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 28 publications
(35 reference statements)
2
39
0
Order By: Relevance
“…34,35 Lifestyle behaviours can affect both consumer behaviour 36 and consumer health. [37][38][39][40][41][42] Lifestyle has been studied as a leading contributor to health outcomes by researchers. 43 Previous research has established that the study of lifestyle behaviours can provide more information about, and a better picture of, individuals than their demographics.…”
Section: Lifestyle Determinants Of Behavioural Outcomes Triggered By mentioning
confidence: 99%
See 3 more Smart Citations
“…34,35 Lifestyle behaviours can affect both consumer behaviour 36 and consumer health. [37][38][39][40][41][42] Lifestyle has been studied as a leading contributor to health outcomes by researchers. 43 Previous research has established that the study of lifestyle behaviours can provide more information about, and a better picture of, individuals than their demographics.…”
Section: Lifestyle Determinants Of Behavioural Outcomes Triggered By mentioning
confidence: 99%
“…44 Unhealthy nutrition, physical inactivity, drug abuse, smoking, alcohol consumption and medicine abuse are common indicators of an unhealthy lifestyle. [41][42][43]45 According to existing studies, engaging in one or more unhealthy lifestyle behaviours advances the risk of death. [46][47][48][49] A meta-analysis revealed that having a healthy lifestyle is linked to a lower risk of death so that a mix of healthy lifestyle behaviours, such as not smoking, moderate alcohol drinking, healthy nutrition, regular physical activity, and having an optimal weight, was linked to a 66% decrease in mortality.…”
Section: Lifestyle Determinants Of Behavioural Outcomes Triggered By mentioning
confidence: 99%
See 2 more Smart Citations
“…Another limitation of this investigation was that the cross-sectional design did not allow us to evaluate the origin-effect factors. Patients with PCAD may have several risk factors such as psychosocial factors, fruit and vegetable consumption, stress and physical activity (38). Molecular analysis of other genes and their pathophysiological effects on the pathogenesis of PCAD, such as TNFRs, needs to be carried out.…”
Section: Linical Findings Among Patients With Pcadmentioning
confidence: 99%